(untitled) (Revista de Estudios Europeos, 2022)
The paper analyse and compare, also in the light of the current pandemic situation, some of the conflicting legal contributions that have alternated over the years with reference to the State Concession Institute, with tourist-recreational purposes, in order to understand the degree of adaptation of our administrative system to the principles imposed by EU law, in particular as regards the protection of competition and equal treatment between operators in the sector.